Using cognitive theory to explain entrepreneurial risk-taking: Challenging conventional wisdom - Palich, Leslie E.; Ray Bagby, D. (Journal of Business Venturing, 1995)
Though it occupies the center of most definitions of entrepreneurship, the concept of risk-taking and its linkages with other constructs (most notably personal traits) have been difficult to capture. As a result, it has been difficult to explain why entrepreneurs rush in to take advantage of opportunities that others fail to see or act upon. However, research on social cognition may shed new light on these challenging issues (Shaver and Scott 1991), providing useful frameworks that differentiate entrepreneurs from others while predicting differences in risk-taking behavior. Within the strategic management literature, Dutton and Jackson (1987) adopted categorization theory as a conceptual framework to explain how decision-makers evoke alternate strategic decision frames. They argue that the attributes of a particular issue cause the decision-maker to categorize that strategic issue in different ways, and this heuristic guides the meaning of a stimulus by directing attention toward some of its elements and away from others. Building upon this work and the knowledge structure literature, Gooding (1989) developed decision frames concerning perceptions of strengths/weaknesses and opportunities/threats. Using distinctive and equivocal data in scenarios, he found that distinctive data tended to evoke the same decision frame in all subjects, whereas equivocal data led to different decision frames among subjects. In other words, in the absence of a particular stimulus (i.e., a scenario is equivocal in nature), individuals tend to resort to a chronic frame of reference when interpreting those data. This research produced some revealing results, but these studies were not constructed to investigate the unique responses of entrepreneurs when faced with common circumstances. To extend this area of inquiry, we designed our study using a scenario approach to determine if entrepreneurs exhibit evidence of unique cognitive categorization processes when they are presented with equivocal data. Our findings proved interesting. As predicted, entrepreneurs did not vary significantly in their responses to a risk propensity scale, meaning that they did not perceive themselves as being any more predisposed to taking risks than nonentrepreneurs. This is consistent with previous findings. However, multivariate tests revealed that entrepreneurs categorized equivocal business scenarios significantly more positively than did other subjects, and univariate tests demonstrated that these perceptual differences were consistent and significant (i.e., entrepreneurs perceived more strengths versus weaknesses, opportunities versus threats, and potential for performance improvement versus deterioration). These results have implications for self-report risk propensity scales. Entrepreneurs may not think of themselves as being any more likely to take risks than nonentrepreneurs, but they are nonetheless predisposed to cognitively categorize business situations more positively. This interpretation leads entrepreneurs to view some situations as “opportunities,” even though others perceive them to have little potential (i.e., the latter view these situations as risky ventures that offer disproportionately low returns relative to their associated risks). These results offer hope to those who aspire to identify and exploit business opportunities, even when they are distracted by the perceived high risk of these ventures. Unlike personal traits, cognitive processes can be changed. That is, if certain aspects of cognition are different for entrepreneurs, or more successful entrepreneurs, these processes can be learned or mastered through programs such as “frame of reference” training. This approach has successfully increased the assessment accuracy of individuals charged with various assignments, including performance rating (cf. Sulsky and Day 1992). These efforts may be adapted for training in opportunity evaluation, allowing those predisposed to negative framing to increase the frequency of correct categorizations. Our results also offer the potential to develop a taxonomy that may help to identify entrepreneurs, a tool that would be useful to firms interested in assessing individuals' natural potential for entrepreneurial behavior. At the same time, systematic differences in cognitive processes may permit the differentiation of entrepreneurs from small business owners, which would be useful since these groups often cannot be determined from the size of an enterprise (i.e., both tend to be associated with smaller ventures). Finally, such a taxonomy would provide the impetus for future research that may further define characteristics of risk-taking and, indeed, the nature of entrepreneurship itself.